Fabrication and Characterization of Alq3 Thin Films (2014)
Alq3 (tris (8-hydroxyquinolate) aluminum) thin films were deposited on glass by thermal evaporation in order to establish the optimal evaporation rates of thin films deposited between 30 to 120nm on a substrate with temperatures between 60 and 120°C. The